2015
DOI: 10.1080/19443994.2014.934731
|View full text |Cite
|
Sign up to set email alerts
|

Application of Central Composite Design approach for dairy wastewater treatment by electrocoagulation using iron and aluminum electrodes: modeling and optimization

Abstract: In this study, response surface methodology approach using Central Composite Design was applied to develop a mathematical model and to optimize process parameters for the COD, color, orthophosphate, TSS, and turbidity removal from dairy wastewater by electrocoagulation process using iron and aluminum electrodes. The second-order regression model was developed to predict the removal efficiencies using Statgraphics Centurion XVI.I software program. The optimum conditions for the COD removal were found to be 5.06… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 51 publications
0
9
0
2
Order By: Relevance
“…To evaluate the significance of the linear, quadratic, or interactive parameters in ANOVA, the sum of square value indicating the significance of a particular variable should be taken into account in addition to the F ‐value and the related Prob > F ‐value. To indicate that a parameter has a significant effect on the response, a high SS (sum of square) value, a high F ‐value, and a low Prob > F ‐value should be obtained by analysis of variance 48,52 . Moreover, it may also be concluded that among the significant parameters, the parameter with the higher F ‐value can be identified as more significant.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the significance of the linear, quadratic, or interactive parameters in ANOVA, the sum of square value indicating the significance of a particular variable should be taken into account in addition to the F ‐value and the related Prob > F ‐value. To indicate that a parameter has a significant effect on the response, a high SS (sum of square) value, a high F ‐value, and a low Prob > F ‐value should be obtained by analysis of variance 48,52 . Moreover, it may also be concluded that among the significant parameters, the parameter with the higher F ‐value can be identified as more significant.…”
Section: Resultsmentioning
confidence: 99%
“…Електрохімічні установки компактні та прості у використанні. Серед електрохімічних методів, що в теперішній час ефективно застосовуються для очищення стічних вод від жирів та білків, необхідно відмітити електрофлотацію та електрокоагуляцію [6][7][8][9][10][11][12].…”
Section: постановка проблемиunclassified
“…The EC treatment was carried out at natural pH using an optimum stirred Fe/AISI 304 cell at j = 30 mA cm −2 for 60 min. After conditioning the filtered wastewater at pH 3.0, the PEF treatment using a 6-W UVA lamp was made with a stirred cell equipped with a (circle) boron-doped diamond (BDD), (triangle) Pt, (inverted triangle) IrO 2 -based, or (diagonal cross) RuO 2 -based anode and an air-diffusion cathode, all of 3 cm 2 area, at j = 100 mA cm −2 and 35 °C for 420 min can be related to the parallel quicker attack of the powerful BDD( • OH) originated from reaction (5) [17,18] on organics, enhancing the mineralization process.…”
Section: Sequential Ec/pef Treatment In the 100-ml Cellmentioning
confidence: 99%
“…Greater effectiveness has been achieved by means of electrochemical technologies. However, little information is still available on their use, being limited to either single electrocoagulation (EC) with Fe or Al anodes [14][15][16][17][18][19], EC coupled with chemical Fenton and ozonation [20] and electro-oxidation (EO) with Pt [21] or dimensionally stables anodes (DSA ® ) [3,22]. More research is then needed to clarify the feasibility of sequential electrochemical processes for treating cheese whey wastewater.…”
Section: Introductionmentioning
confidence: 99%